Study of a novel method to assist in early reporting of sepsis from the microbiology laboratory - Purabi Barman; Sharmila Sengupta; Shefali Singh (Journal of Infection in Developing Countries)
Introduction: Microbiology laboratories must provide accurate blood culture reports with rapid turnaround time (TAT) to effectively manage patients with sepsis. In this study three methods are compared for reporting blood culture results: a manual method that included use of a serum separator tube (SST),   the conventional manual, and an automated method for identification and susceptibility (ID/AST).